A study of Emperor Maurice's book on the Byzantine military strategy (Mourice's Strategikon) at the end of the sixth century AD (582-602 AD) (Damascus University Journal of Historical Studies, 2024)
The research entitled (studying the Book of Emperor Maurice on the Byzantine Military Strategy in the late sixth century AD 582-602 AD)dealt with different aspects of the military strategy and tactics used by the byzantine Army in the late sixth century AD.This book is attributed to Emperor Maurice, who ruled in byzantine Empire between the years( 582-602 AD),and the research is considered one of the important topics for its authenticity , and for the importance of the of this source ,which reflects the daily life of the military commander, the names and titles of the army commanders,        and what is related to the methods of training and preparation for the battle, as it provides important and valuable details for historians and those interested in the history of war and its arts.The approach used in this research is the descriptive and analytical approach, where an accurate and comprehensive description of all sections of this book was presented ,and the extent to which the principles and instructions cited by Emperor Maurice were applied were analyzed from the practical application side, and on the ground and the extent of the impact of these instructions and principles on the subsequent intellectual and their reflection on the military forces of the Byzantine Empire ,which were credited with achieving many victories over their enemies.
Keywords: Emperor Maurice; Byzantine military strategy; sixth century AD